2021
DOI: 10.1590/1980-265x-tce-2020-0240
|View full text |Cite
|
Sign up to set email alerts
|

Standard Precaution Adherence by Nursing Workers: A Mixed Methods Study

Abstract: Objective: to analyze standard precaution adherence and associated factors of nursing workers at a university hospital. Method: this is a study of mixed methods of convergent parallel strategy, carried out in Southern Brazil. The quantitative stage had 602 participants, using the instrument of sociodemographic and professional variables and the Instrument of Variables Related to Standard Precautions, analyzed using descriptive statistics. In the qualitative stage, a semi-structured interview was conducted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…O principal modo de transmissão é a quebra da barreira de proteção. Portanto, conhecer e realizar o uso adequado de máscaras, gorros, luvas, aventais, capas para sapatos, óculos ou protetores faciais e realizar a higiene das mãos com água e sabonete líquido ou solução alcoólica a 70% é fundamental 39 .…”
Section: Discussionunclassified
“…O principal modo de transmissão é a quebra da barreira de proteção. Portanto, conhecer e realizar o uso adequado de máscaras, gorros, luvas, aventais, capas para sapatos, óculos ou protetores faciais e realizar a higiene das mãos com água e sabonete líquido ou solução alcoólica a 70% é fundamental 39 .…”
Section: Discussionunclassified
“…The increasing temporal trend in the incidence of percutaneous accidents among workers with a time equal to or greater than 61 months of professional experience in the hospital can be explained by behavioral factors, such as difficulty in adhering to training ( 32 ) and overconfidence to perform procedures invasive ( 15 , 28 ) . Despite the existence of PCMs and resources necessary to carry out safe work, it is often observed that more experienced health professionals put themselves at risk of an occupational accident, even in the possibility of contamination ( 33 - 34 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Um estudo que analisou a tendência temporal da taxa de lesões percutâneas em um hospital durante a implantação progressiva de MP com dispositivos de segurança para substituir MP convencionais observou uma tendência de queda entre profissionais (auxiliares de enfermagem) que possuem ensino médio (31) . A tendência temporal crescente da incidência de acidentes percutâneos entre os trabalhadores com tempo igual ou superior a 61 meses de experiência profissional na instituição hospitalar pode ser explicada pelos fatores comportamentais, como a dificuldade de adesão aos treinamentos (32) e excesso de confiança para realizar procedimentos invasivos (15,28) . Apesar de existirem as MCPs e recursos necessários para a realização de um trabalho seguro, observa-se com frequência profissionais da saúde mais experientes se colocando em situação de risco de acidente ocupacional, mesmo na possibilidade de contaminação (33)(34) .…”
Section: Sexounclassified